Effect of plant density and bio fertilization on some growth and yield traits of two peanut cultivars - حربا, رحاب; مجد درويش,; سمير الأحمد ,; ياسر حماد , (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out during the agricultural season 2022 at Zahid Station for Water and Irrigation Research- Agricultural Scientific Research Center in Tartous, to study the effect of planting density (20×50 and 30×50 cm) and spraying with EM1 biofertilizer (control without spraying, 3 ml/L, 6 ml/L) on some vegetative growth and productivity characteristics of two peanut varieties (Giza 6 and Syrian 2): such as plant height, number of leaves, green weight of the plant, weight of 1000 seeds, number of pods/plant and the yield of dry pods per hectare. The randomized complete block design was used according to the split-plot arrangement twice for the studied treatments, as the agricultural density occupied the main plots, the bio-fertilization sub-plots and the sub-plot variety, and the treatments were randomly distributed in three replications. The results showed that the Giza 6 variety was significantly superior to the Syrian 2 variety in all studied traits, and the planting density (30×50 cm) was significantly superior to the density (20×50 cm) in terms of the number of leaves (375.7 and 313.97 leaves), and the green weight of the plant (639.45 and 577.89 g) and the weight of 1000 seeds were (1131.37 and 947.63 g), while the plant density (20×50 cm) was significantly superior in plant height and hectare productivity of dry pods. As for the effect of biofertilization on the studied traits, the treatment with two concentrations 3 and 6 ml/L was significantly superior to the control, and the concentration of 6 ml/L was significant in terms of significant increase in the values of plant height, number of leaves, green weight of the plant, weight of 1000 seeds and the productivity of dry pods per hectare. The results concluded that cultivating Giza 6 at a density of 30×50 cm and spraying it with 6 ml/L of EM1 gave the highest value for the number of leaves/plant, the green weight of the plant and the weight of 1000 seeds, while cultivating it at a density of 20×50 cm gave a significant positive effect that was greater for plant height and yield than dry pods/ha.